Factors Affecting People’s Attitudes towards Cricket: with Special Reference to Kandy Sectarian Division - Weerakoon, W.M.R.K.; Jayantha, K.; Ubayachandra, E.G. (University of Jaffna, 2012)
As the most popular and widely spaded sport in Sri Lanka, it was selected the particular topic titled ‘factors affecting people's attitude towards cricket: with special reference Kandy sectarian division’. At the point of hosting the Sri Lanka team in the final match of widely spread some disappointment among the cricket spectators and others interested general public. The researcher was stimulated by this unpleasant climate and unsolved problem created such on what happened to people's attitude towards cricket. For studying on this problem, Present paper was conducted. There were two objectives expected to fulfill by the study namely. (i) to understand the people's attitude toward cricket after the World Cup 2011 and (ii) to identify the people's attitude toward cricket in order to demographic factors such on age, gender, and level of education. Hence this study was based on three predictions namely, (i) gender make different attitude on cricket (H1), (ii) there is a negative correlation between attitude toward cricket and age (H2), and (iii) there is a negative correlation between attitude toward cricket and level of education (H3). At the point of testing this hypotheses, the study was limited to a sample population for the convenience of the study, Kandy sectarian division, where in located the Pallekale international cricket ground and one game of world cup 2011 was held selected on the study area, purposely, five other sub divisions selected, those were located around the ground, and sample size of each division was selected proportionate to the sub division population. Then respondents were chosen by simple random sampling technique with association of divisional registration unit and random number table. The data were collected from the respondents by exploring a questionnaire that was carefully conducted according to the likert scale method. A total of 250 questionnaires were distributed among the sample on the basis of quota given to the each sub division, by using the data collected though the survey. The three hypotheses were tested using a statistical software. The results show that very weak negative correlation both age and level of education with attitude towards cricket. Gender and attitude towards cricket also shows a very weak negative skiwness. Based on the findings of the study number of recommendations was made to the sports authorities and researchers in the field of sport sciences to improve attitude about Cricket in the country in future. Resulting from implementation, of given recommendations, the respective benefits will be yielded by Sri Lankan sports, at aggregate level